0710 Hypoglossal Neurostimulation In Rem- Vs. Nrem-predominant Obstructive Sleep Apnea. (27th May 2020) - Cabrera, C I; Szelestey, B; Strohl, K; Schell, A
Abstract: Introduction: Obstructive sleep apnea (OSA) is a chronic condition that requires appropriate treatment strategies to optimize outcomes while minimizing risk. In addition to anatomy, physiologic factors such as arousal threshold and loop gain (i.e. "endotypes") play a known role in the disease process. Because loop gain tends to be higher and arousal threshold lower in NREM sleep, we hypothesize that patients with NREM-predominance may achieve less success with anatomical therapy such as upper airway stimulation (UAS). Our study aims to evaluate baseline characteristics and objective results related to NREM-predominance in patients treated with UAS. Methods: Using data from the STAR trial, we identified patients (n=103) with at least 20 minutes of REM on baseline testing and complete demographic and disease data at baseline and month 18. Baseline NREM-predominant disease (percent NREM events > 50) was defined as a binary variable. We created two cohorts: 1) patients with REM-predominant disease and 2) those with NREM-predominant disease. ODI and AHI were evaluated at month 18. Results: Overall 62% (n=64) of patients had NREM-predominant disease at baseline. Other baseline characteristics were similar between both groups. In univariate analysis, age was significantly associated with lower AHI in the NREM-predominant population (p<0.05) but not in the REM-predominant group (p>0.05). Results were similar for ODI. For both groups, increasing age was correlated negatively with increasing AHI; this correlation was stronger in the NREM-predominant group Conclusion: A majority of patients in the STAR trial had NREM-predominant OSA at baseline. There appears to be an interaction between NREM-predominance and age as predictors of UAS outcomes. Support: